Children With Congenital Unilateral Sensorineural Hearing Loss: Effects of Late Hearing Aid Amplification—A Pilot Study. Issue 1 (January 2020) - Johansson, Marlin; Asp, Filip; Berninger, Erik
Abstract : Objectives: Although children with unilateral hearing loss (uHL) have high risk of experiencing academic difficulties, speech-language delays, poor sound localization, and speech recognition in noise, studies on hearing aid (HA) outcomes are few. Consequently, it is unknown when and how amplification is optimally provided. The aim was to study whether children with mild-to-moderate congenital unilateral sensorineural hearing loss (uSNHL) benefit from HAs. Design: All 6- to 11-year-old children with nonsyndromic congenital uSNHL and at least 6 months of HA use were invited (born in Stockholm county council, n = 7). Participants were 6 children (9.7- to 10.8-years-old) with late HA fittings (>4.8 years of age). Unaided and aided hearing was studied with a comprehensive test battery in a within-subject design. Questionnaires were used to study overall hearing performance and disability. Sound localization accuracy (SLA) and speech recognition thresholds (SRTs) in competing speech were measured in sound field to study hearing under demanding listening conditions. SLA was measured by recording eye-gaze in response to auditory-visual stimuli presented from 12 loudspeaker–video display pairs arranged equidistantly within ±55° in the frontal horizontal plane. The SRTs were measured for target sentences at 0° in spatially separated (±30° and ±150°) continuous speech. Auditory brainstem responses (ABRs) were obtained in both ears separately to study auditory nerve function at the brainstem level. Results: The mean ± SD pure-tone average (0.5, 1, 2, and 4 kHz) was 45 ± 8 dB HL and 6 ± 4 dB HL in the impaired and normal hearing ear, respectively (n = 6). Horizontal SLA was significantly poorer in the aided compared with unaided condition. A significant relationship was found between aided SLA (quantified by an error index) and the impaired ear's ABR I to V interval, suggesting a relationship between the two. Results from questionnaires revealed aided benefit in one-to-one communication, whereas no significant benefit was found for communication in background noise or reverberation. No aided benefit was found for the SRTs in competing speech. Conclusions: Children with congenital uSNHL benefit from late HA intervention in one-to-one communication but not in demanding listening situations, and there is a risk of degraded SLA. The results indicate that neural transmission time from the impaired cochlea to the upper brainstem may have an important role in unilaterally aided spatial hearing, warranting further study in children with uHL receiving early HA intervention. Abstract : Supplemental Digital Content is available in the text.